High prevalence of syphilis, HBV, and HCV co‐infection, and low rate of effective vaccination against hepatitis B in HIV‐infected patients in West China hospital. Issue 1 (10th October 2017) - Yang, Tingting; Chen, Qixia; Li, Dongdong; Wang, Tingting; Gou, Yu; Wei, Bin; Tao, Chuanmin
Abstract : To investigate the epidemiological features and risk factors of HBV, HCV, and syphilis infection among HIV‐infected patients in West China Hospital. A retrospective study was conducted with HIV‐infected patients from 2014 to 2016 in West China hospital, SCU. Serum makers for HBV, HCV, and syphilis were detected. Among 894 HIV‐infected patients, the prevalence of HIV/HBV, HIV/HCV, HIV/syphilis co‐infections was 14.4%, 5.7%, and 18.9% respectively. HIV/HBV/HCV, HIV/HCV/syphilis, and HIV/HBV/syphilis triple co‐infection was 7 (0.7%), 12(1.3%), 29(3.2%) respectively. The rate of effective vaccination against HBV was only 7.7% in HIV‐infected patients. Age (OR = 0.243 95% CI: 0.114 −0.518), ethnicity (OR = 3.654 95% CI: 1.849‐7.218) and education level (OR = 0.140 95% CI: 0.033‐0.606) are risk factors affecting HIV/HCV co‐infection. A high prevalence of HIV/syphilis, HIV/HBV, and HIV/ HCV co‐infection can be observed in west China. The rate for HIV‐infected patients who were effectively vaccinated against HBV was fewer than 10%. Abstract : There was high prevalence of HIV/syphilis, HIV/HBV and HIV/HCV co‐infection in west China. And fewer than 10% of HIV‐infected patients were effectively vaccinated against HBV in west China. Age, ethnicity and education level are risk factors affecting HIV/HCV co‐infection. The transmission route of HIV and HBV co‐infection is one of its risk factor. Hepatitis virus and syphilis screening is suggested to be included in routine monitoring of HIV infection.